A METHOD OF MEASURING SNOW PARTICLE SIZE FROM VIDEO IMAGES FOR METEOROLOGICAL RADAR OBSERVATIONS - ハタナカ, マサヒコ; オオタ, ヨシユキ; ニシツジ, アキラ; サカグチ, タケシ; ワダ, マコト; HATANAKA, Masahiko; OHTA, Yoshiyuki; NISHITSUJI, Akira; SAKAGUCHI, Takeshi; WADA, Makoto (National Institute of Polar Research, 1995)
P(論文) For meteorological radar observations, it is very important to know the size and the characteristics of precipitation particles. In this paper, we report a method to measure snow particle size using snow particle video images. An image of snow particles, which was recorded by a specially designed portable video camera set on the ground, was digitized by a popular-priced personal computer. To reduce background offset, we used subtraction processing between images at different recording times. Using projection data on this image, the position of each snow particle was detected. Finally, we measure the three kinds of snow particle "radius". We applied this method to two sets of VCR tapes that had been recorded at Syowa Station, Antarctica, on April 5-6 and on October 1,1988,and obtained relative distributions. departmental bulletin paper